Guidelines for the Preparation of Feasibility Reports for Coal Projects - Planning Commission (Planning Commission, 1992)
The quality of appraisal, investment decision and success of the projects depend largely on the quality and content of the Feasibility Report(FR).It is in this context that the Planning Commission had earlier issued guidelines for the preparation of FR in 1966 and later in January, 1975. The 1975 version of the guidelines relates to the industrial projects but the same has been in use in other sectors as well to the extent possible.
Project Appraisal Division Planning Commission Government of India
Project Appraisal Division Planning Commission Government of India